THE VALUE OF SYSTEMIC INFLAMMATORY BIOMARKERS IN ASSESSING SEVERITY IN PATIENTS WITH CEREBRAL INFARCTION (Vietnam Journal of Community Medicine, 2026)
Objective: Comparison of systemic inflammatory markers NLR, CRP, and interleukin-6 between patients with acute ischemic stroke and controls, and evaluation of the value of these inflammatory biomarkers in assessing stroke severity according to the NIHSS score. Subjects and Methods: Cross-sectional study with control group was conducted, including 113 patients with cerebral infarction and 113 control subjects. Inflammatory markers assessed comprised neutrophil count, lymphocyte count, neutrophil-to-lymphocyte ratio (NLR), C-reactive protein (CRP), and interleukin-6 (IL-6). Disease severity was evaluated using NIHSS score. Results: The mean age was 65.03 ± 10.75 years, with 25.7% of patients having NIHSS ≥15. NLR was higher in the patient group compared to controls (4.11 vs 2.31; p
Keywords: Cerebral infarction, inflammatory biomarkers, neutrophil-to-lymphocyte ratio (NLR), C-reactive protein (CRP), interleukin-6 (IL-6).